Neighbourhood structure and environmental quality: A fine-grained analysis of spatial inequalities in urban Germany - Christian König (Urban Studies, 2024)
Urban environments are characterised by sparsity of space, elevated levels of air pollution and limited exposure to natural environments. Yet, residential environmental quality varies substantially both between and within cities. This study combines information on the socio-economic and demographic composition of 243,607 urban neighbourhoods with administrative and remote sensing data on the spatial distribution of industrial plants and urban green space to investigate patterns of environmental inequality in urban Germany at unprecedented levels of spatial granularity. It disentangles neighbourhood disadvantages experienced by foreign minorities (non-nationals) from those experienced by low-income households in order to assess the plausibility of economic explanations of residential sorting. The high level of spatial granularity makes it possible to examine patterns of environmental inequality not only between the relatively large areas that have been used as units of analysis in previous work but also within them, while reducing the threat of ecological bias. Results indicate that non-nationals are more likely to be exposed to industrial air pollution and less likely to live close to green spaces. This association holds even after adjusting for neighbourhood income composition and in fixed-effects specifications that restrict the analysis to within-city variation. I find no evidence for environmental inequality by socio-economic status. Exploratory sub-sample analyses show that neighbourhood disadvantages for non-nationals are higher in cities characterised by high levels of anti-foreigner sentiment, pointing towards housing market discrimination as a potentially important driver of foreign residents' neighbourhood disadvantage.
Keywords: 300; environmental justice; inequality; land use; method; neighbourhood; race/ethnicity; residential sorting and segregation